RELATIONSHIP OF BODY FAT PERCENTAGE AND APO B/APO A-1 RATIO AS CARDIOVASCULAR RISK MARKER IN RURAL ADULTS OF YOGYAKARTA INDONESIA - ., Fenty; Widayati, Aris; Hendra, Phebe (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: Prevalence of obesity and cardiovascular disease has increased in both urban and rural areas Indonesia. High body fat percentage (BF%) is associated with a high cardio metabolic risk. The apolipoproteins (Apo) B/Apo A-1 ratio is a better risk predictor for cardiovascular disease. This study aimed to explore the relationship of BF% and Apo B/Apo A-1 ratio among rural adults in Yogyakarta Indonesia. Methods: This cross-sectional study included 40 men and 62 women (40-60 y old). Those who had cardiometabolic diseases, edema or currently taking cardio metabolic medicines were excluded. Information about sociodemographic details was obtained by using a self-administerd questionnaire. The questionnaire also assessed smoking status, reproductive history and medical history. Anthropometric measurement, apo B, Apo A-1, fasting blood glucose and blood pressure were measured. Results: The prevalence of high BF% was 12.7% and 6.9% in men and women, respectively. There was negative correlation between BF% and apo A-1 and positive correlation between BF% and apo B as well as BF% and apo B/apo A-1 ratio. A significant weak correlation was observed between BF%-apo B/apo A-1 ratio in women (r: 0.280; p: 0.027). Conclusion: BF% is associated with apo B/apo A-1 ratio among women adults in rural area of Yogyakarta Indonesia findings support the importance of using BF% to predict cardiovascular disease in rural area.